Kegagalan Tata Kelola dan Elite Capture pada Dana Desa: Sebuah Meta Sintesis Literatur Akuntansi Sektor Publik - Icha Mustamin; Andi Rafiyadi Eka Saputra; Nirwana Nirwana; Aini Indrijawati (AKUNTANSI 45, 2026)
Fiscal decentralization through the Village Fund is idealized as an instrument for economic equality and democratic governance at the grassroots level. However, contemporary public sector accounting literature reveals an anomaly: high levels of administrative compliance do not correlate with substantive accountability. This paper, a Systematic Literature Review (SLR), aims to synthesize previous empirical findings regarding governance failures and the phenomenon of elite capture in Village Fund management in Indonesia. Using a qualitative meta-synthesis approach from leading journal articles, this study finds that the failure of Village Fund governance is caused by three main factors: (1) institutional separation due to the forced adoption of the formal system (SISKEUDES) without cultural readiness; (2) the dominance of a paternalistic culture that inhibits rational participation; and (3) a deficit in citizen political articulation. These findings confirm that without strong political articulation, the formal accounting system will only serve as an instrument of legitimacy for the village oligarchy. The implications of this study call for a paradigm shift in public sector auditing from compliance auditing to liberating social auditing.